Implementasi Kurikulum Pendidikan Jasmani di Institute of Technical Education College East, Singapore Tahun 2018 (Indonesian Journal for Physical Education and Sport, 2021)
Abstract ITE College East Singapore is a post-secondary education institution that emphasizes students on career, technical, and skills education. The purpose of this study is to describe and analyze the Physical Education Curriculum implementation at ITE College East Singapore. The research used a qualitative descriptive approach with the CIPP model’s assist. The results showed that in the context aspect, ITE College East is a formal pre-university educational institution under Singapore Ministry of Education. Input aspects consist of students having talents and interests in practical skills. Curriculum emphasizes cognitive, motor skills, and the formation of student’s personality values. Teachers have required qualifications and competencies. Suffice and standardized facilities. The process aspect is learning activities lesson plan with the game concept approach, the use of media is used to support learning activities, and the teacher carries out the teacher’s administrative tasks. In product aspect, the learning outcomes of students show that they have exceeded the Grading System and Grade Point Average, students’ achievement that have been achieved are related to academic achievement and the Co Currucular Activity championship, and some graduates of ITE College East directly working and some others continue to polytechnic. The conclusions of this research shows the physical education curriculum implementation at ITE College East has well-worked illustrated in the context, input, process and product aspects.